Managers' pay duration and voluntary disclosures - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2014)
In this paper, we examine the effect of managers’ pay duration on firms’ voluntary disclosures. Pay duration refers to the average period that it takes for managers’ annual compensation to vest. We hypothesize and find that pay duration can incentivize managers to provide more bad news earnings forecasts. This result holds after controlling for the level of stock-based compensation and the endogeneity of pay duration. In addition, we find that the effect of pay duration is more pronounced for firms with weaker governance and for firms with a more opaque information environment, where the marginal benefits of additional disclosures are higher. Our additional analyses indicate that managers with a longer pay duration issue more accurate earnings forecasts. Overall, our paper contributes to the literature by documenting that lengthening the vesting periods of managers’ compensation can induce managers to be more forthcoming with bad news.